The Existence of Faults that Cause Earthquakes on Lombok Island: A Critical Literature Review - I Gusti Ketut Satria Bunaga; Mohammad Syamsu Rosid; Titi Anggono (Postgraduate, University of Mataram, 2022)
This study qualitatively elaborates fault characteristics causing earthquakes in Lombok Island. Historically, Lombok Island has been 12 destructive and significant earthquakes in period of 1979 – 2018. Therefore, the island is in an earthquake-prone region. The hazard factor is one of the key factors in assessing risk. This study become important as their potential to have a big impact. A source of activity that has not been fully investigated in detail was the location of the recent major and devastating earthquake (East Lombok earthquake 2019). Consequently, there is a chance that the level of risk on the Island of Lombok will rise. According to the study’s results, a thorough investigation is required to identify and pinpoint the cause of the 2019 Lombok earthquake in order to improve the earthquake risk index and help the local government to reduce losses due to earthquakes.